2021
DOI: 10.1061/(asce)st.1943-541x.0003129
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of High-Strength and Ultrahigh-Performance Concrete Targets Subjected to Relatively Rigid Projectile Impact

Abstract: This experimental study was conducted to evaluate the impact behavior of relatively rigid projectiles with conical and hemispherical nose shapes on normal to high-strength and ultrahigh performance concrete (UHPC). For this impact experiment, target specimens with dimensions of 200 × 200 × 100 mm and concrete compressive strengths of 35, 80, 100, 120, and 150 MPa were used. The test results showed that as the concrete strength increased, the penetrability of concrete normalized by the kinetic energy of each pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Additionally, as the target strength increased, there was a slight decrease in penetration depth. Kim [15] conducted penetration tests on five concrete targets of varying strengths using conical and hemispherical projectiles. The research indicated that the penetration depth decreased as the concrete strength increased.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as the target strength increased, there was a slight decrease in penetration depth. Kim [15] conducted penetration tests on five concrete targets of varying strengths using conical and hemispherical projectiles. The research indicated that the penetration depth decreased as the concrete strength increased.…”
Section: Introductionmentioning
confidence: 99%